To solve the equation \(x^2 - 8x + 12 = 0\) using the Quadratic Formula, we first identify the coefficients:
- \(a = 1\)
- \(b = -8\)
- \(c = 12\)
The Quadratic Formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Now, let's calculate the discriminant \(b^2 - 4ac\):
\[ b^2 - 4ac = (-8)^2 - 4(1)(12) = 64 - 48 = 16 \]
Since the discriminant is positive (\(16 > 0\)), there will be two real solutions.
Now we apply the Quadratic Formula:
\[ x = \frac{-(-8) \pm \sqrt{16}}{2 \cdot 1} = \frac{8 \pm 4}{2} \]
Now we can find the two solutions:
-
First solution: \[ x = \frac{8 + 4}{2} = \frac{12}{2} = 6 \]
-
Second solution: \[ x = \frac{8 - 4}{2} = \frac{4}{2} = 2 \]
Thus, the solutions to the equation \(x^2 - 8x + 12 = 0\) are:
A. \(x = 6, 2\)
So, the final answer would be:
Answer: \(x = 6, 2\)